1999
DOI: 10.1111/j.1365-2621.1999.tb09852.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Oxidation, Volatiles and Color Changes of Irradiated Pork Patties Affected by Antioxidants

Abstract: Changes were measured in TBARS, color, and volatiles of irradiated (4.5 kGy) pork patties with antioxidants (sesamol, quercetin, rutin, BHT, and rosemary oleoresin) during 7 days storage at 48C. Irradiation accelerated lipid oxidation of raw pork during storage. However, irradiation before cooking did not influence lipid oxidation of cooked pork during storage. Sesamol, quercetin, and BHT were effective in both irradiated raw and cooked pork during 7-days storage. Rosemary oleoresin and rutin were effective on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 24 publications
7
59
0
Order By: Relevance
“…Chen et al (1999) also reported that the presence of a natural antioxidant positively affected the lightness of pork patties. These authors compared the effect of rosemary oleoresin with BHT and found that the natural antioxidant had a strong antioxidant effect stabilizing product coloration.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al (1999) also reported that the presence of a natural antioxidant positively affected the lightness of pork patties. These authors compared the effect of rosemary oleoresin with BHT and found that the natural antioxidant had a strong antioxidant effect stabilizing product coloration.…”
Section: Resultsmentioning
confidence: 99%
“…Lee and Ahn (2003) found that phenolic compounds such as gallate and sesamol were effective antioxidants in reducing TBARS in turkey breast during 5 days of storage. Chen et al (1999) reported that phenolic compounds such as quercetin were also effective in preventing lipid oxidation in both raw and cooked turkey during 7 days of storage. According to study conducted by Yigit et al (2009) in another prunus variety (apricot) the highest percent inhibition of lipid peroxidation was found 68.6%/100 μg solid in methanol extracts of the sweet kernel.…”
Section: Whc and Cooking Loss Of Ground Meat Treated With Tce And Psementioning
confidence: 99%
“…Lee and Ahn (2003) found that phenolic compounds such as gallate and sesamol were effective antioxidants in reducing TBARS in turkey breast during 5 days of storage. Chen et al (1999) reported that phenolic compounds such as quercetin were also effective in preventing lipid oxidation in both raw and cooked turkey during 7 days of storage. In another study methanolic extract of some legume were effective in the protection of lipids and non-lipids against various oxidative model systems.…”
Section: Reducing Powermentioning
confidence: 99%